Effects Of Adjuvant Honey Therapy On Disease Activity, Lymphocyte Function And Lymphocyte Subsets In Patients With Systemic Lupus Erythematosus - Mohamad, Wathik M. (2009)
SLE is a prototype autoimmune disease which can affect many tissues and organs of the body. Current treatment with anti-inflammatory and immunosuppressive drugs are able to suppress disease activity but associated with significant short term and long term side effects. SLE merupakan prototaip autoimun yang boleh melibatkan banyak tisu dan organ badan. Rawatan terkini menggunakan dadah anti-radang dan dadah penindas imun berkebolehan untuk menindas aktiviti imun tetapi mempunyai kesan sampingan jangkamasa pendek dan jangkamasa panjang yang signifikan.